WAYS TO PREVENT CHILDREN'S DISEASES AND TREAT THEM WITH MODERN METHODS IN MEDICINE - Ruziyeva Khilola,Zakirova Farangiz (International Journal of Literature and Language Studies, 2026)
This article discusses the methods of prevention, early diagnosis and modern treatment of common infectious and non-communicable diseases among children. Recommendations are given on vaccination, adherence to hygiene standards, and strengthening the immune system of children as preventive measures. The importance of treatment methods based on innovative technologies, in particular physiotherapy, modern antibiotics, an individual approach and telemedicine services, is also considered. The article contains scientific and practical recommendations aimed at improving children's health in the healthcare system.